2002
DOI: 10.1046/j.1365-2109.2002.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of refractometry as a method of determining blood total protein concentration in the American lobsterHomarus americanus(Milne Edwards)

Abstract: Given the high unit value of live American lobsters (Homarus americanus), a non‐destructive field method to assess physiological state is desirable during out‐of‐water transport conditions. This study compared an Uricon® specific gravity refractometer, with a commercial veterinary blood analyser (Vet‐Test), as a method for determining the blood total protein concentration in live, out‐of‐water individuals. Regression analysis of R2 = 0.8641 (n = 64) was observed in determination of blood total protein concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…However this long-term upregulation of general immunity depletes resources and comes with a metabolic cost, seen as a reduced adult haemolymph protein load in immune-challenged individuals. Protein load of the haemolymph has been used as an adequate indicator of physiological metabolic condition (Ozbay & Riley 2002;Nakamatsu & Tanaka 2003) and disease resistance (Adamo 2004) in invertebrates. Nymphal nutritional condition positively affected lysozyme activity, while there was no effect on the proPO cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However this long-term upregulation of general immunity depletes resources and comes with a metabolic cost, seen as a reduced adult haemolymph protein load in immune-challenged individuals. Protein load of the haemolymph has been used as an adequate indicator of physiological metabolic condition (Ozbay & Riley 2002;Nakamatsu & Tanaka 2003) and disease resistance (Adamo 2004) in invertebrates. Nymphal nutritional condition positively affected lysozyme activity, while there was no effect on the proPO cascade.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a measure of physiological condition we assessed the total protein load of the haemolymph (Ozbay & Riley 2002;Nakamatsu & Tanaka 2003). The concentration of total protein was determined photometrically in 5 ml of diluted haemolymph, using the test solution Roti Nanoquant (K 880.1, Carl Roth GmbH & Co., Karlsruhe, Germany), following the protocol of the manufacturer.…”
Section: (F) Haemolymph Protein Loadmentioning
confidence: 99%
“…Levels of prophenoloxidase in lobsters are known to fluctuate in response to environmental changes and stress (Moullac & Haffner 2000) and they, together with the level of protein in the hemolymph, have been used as an indicator of lobster health (Chang, 1995;Floreto et al, 2000;Osbay & Riley 2002). Comparison of prophenoloxidase levels between 540 P. cygnus sampled in this study and a database of 119 P. cygnus lobsters (both wild caught and wild captive) has revealed that all but one of the test animals were within normal range for prophenoloxidase and similar to some of the larger wild caught lobsters (B. Jones, unpublished data).…”
Section: Lobster Healthmentioning
confidence: 99%
“…Leavitt and Bayer (1977) used a total solids refractometer as a way to analyze THP levels directly in the field without returning to a laboratory to use a spectrometer or other laboratory protocol. This refractometer procedure has since been universally adopted by the lobster industry and is now the most common technique used to determine lobster vitality (Ozbay 1996, Ozbay & Riley 2002. Unfortunately, all techniques to quantify THP, including refractometry, are invasive in that they require drawing a hemolymph sample with needled syringe.…”
Section: Introductionmentioning
confidence: 99%